A surface‐potential‐based MOSFET compact model accounting for random doping fluctuations. (17th December 2013) - Donati Guerrieri, S.; Cappelluti, Federica; Bonani, Fabrizio; Ghione, Giovanni; Crupi, Giovanni; Schreurs, Dominique; Caddemi, Alina
SUMMARY We present a compact, surface‐potential‐based modeling approach for deeply scaled digital or radio‐frequency metal‐oxide‐semiconductor field‐effect transistor able to account for random doping fluctuations in the device channel. Random dopant fluctuations are one of the primary causes for device variability in nanometer‐scale components. The present approach is based on the Green's function formulation of the device external electrical parameters (such as the output current) small‐change sensitivity to distributed, space‐dependent doping variations in the channel; furthermore, the methodology is used also to assess the small‐signal device parameter variations within the limits of a quasi‐static description. The present approach allows for an efficient circuit‐level sensitivity analysis and has been applied to the PSP compact model through a Verilog‐A code implemented within the ADVANCED DESIGN SYSTEM (Agilent Technologies, Santa Clara, CA, U.S.A.) simulator. Examples are provided to show that the model predictions are in good agreement with far more time‐consuming simulations. Copyright © 2013 John Wiley & Sons, Ltd.